Titanium nanoparticles activate a transcriptional response in Arabidopsis that enhances tolerance to low phosphate, osmotic stress and pathogen infection - Pérez-Zavala, Francisco Gabriel; Atriztán-Hernández, Karina; Martínez-Irastorza, Paulina; Oropeza-Aburto, Araceli; López-Arredondo, Damar; Herrera-Estrella, Luis (Frontiers in Plant Science, 2022)
Titanium is a ubiquitous element with a wide variety of beneficial effects in plants, including enhanced nutrient uptake and resistance to pathogens and abiotic stresses. While there is numerous evidence supporting the beneficial effects that Ti fertilization give to plants, there is little information on which genetic signaling pathways the Ti application activate in plant tissues. In this study, we utilize RNA-seq and ionomics technologies to unravel the molecular signals that Arabidopsis plants unleash when treated with Ti. RNA-seq analysis showed that Ti activates abscisic acid and salicylic acid signaling pathways and the expression of NUCLEOTIDE BINDING SITE-LEUCINE RICH REPEAT receptors likely by acting as a chemical priming molecule. This activation results in enhanced resistance to drought, high salinity, and infection with Botrytis cinerea in Arabidopsis. Ti also grants an enhanced nutritional state, even at suboptimal phosphate concentrations by upregulating the expression of multiple nutrient and membrane transporters and by modifying or increasing the production root exudates. Our results suggest that Ti might act similarly to the beneficial element Silicon in other plant species.